Differences in the seasonality of Middle East respiratory syndrome coronavirus and influenza in the Middle East. (November 2015) - He, Daihai; Chiu, Alice P.Y.; Lin, Qianying; Cowling, Benjamin J.
Highlights: It was found that the first two major waves of weekly laboratory confirmations of MERS-CoV cases closely followed the seasonal epidemic waves of influenza A in the Middle East. This finding is important to revealing the mechanisms behind the seasonality of MERS-CoV in the Middle East.